Generation, Characterization and Collection of Solid Waste - A Case Study - Siddiqui, Dr. Lubna (IJRDO-Journal of Applied Science, 2015)
The study deals with generation and characterization of solid waste in class II town of district Ambedkar Nagar, Uttar Pradesh. With an average waste generation rate of 0.350 kg/head/day, the town generates about 28.672 ton of waste daily. As per our estimates nearly 63.95 per cent population generates 75.38 per cent waste at the rate of more than 0.300 kg/head/day and only 11.77 per cent population generates less than 0.25 kg/head/day. The share of organic waste is well below 50 per cent. The average organic waste generation rate is 0.158 kg/head/day, whereas average inorganic waste generation is 0.198 kg. Only 35 per cent waste is collected.